ElasticSearch cookbook : over 130 advanced recipes to search, analyze, deploy, manage, and monitor data effectively with ElasticSearch /: over 130 advanced recipes to search, analyze, deploy, manage, and monitor data effectively with ElasticSearch. (2015) - Paro, Alberto
No abstract available